Refiguring melodrama in film and television : captive affects, elastic sufferings, vicarious objects - Zarzosa, Agustín, 1970- (Lexington Books, 2013)
Refiguring Melodrama in Film and Television: Captive Affects, Elastic Sufferings, Vicarious Objects, by Agustín Zarzosa, challenges the long-standing definition of melodrama as a cultural mode that anxiously proclaims the existence of a defunct moral order in a post-sacred world. Arguing that the central concern of melodrama is not morality but suffering, this book offers an alternative conception of melodrama as an apparatus that shapes suffering and redistributes its visibility.